Factors associated with receptive injection equipment sharing among people who inject drugs: findings from a multistate study at the start of the COVID-19 pandemic - Sean T. Allen; Kristin E. Schneider; Miles Morris; Saba Rouhani; Samantha J. Harris; Brendan Saloner; Susan G. Sherman (BMC, 2023)
Abstract Background Receptive injection equipment sharing (i.e., injecting with syringes, cookers, rinse water previously used by another person) plays a central role in the transmission of infectious diseases (e.g., HIV, viral hepatitis) among people who inject drugs. Better understanding these behaviors in the context of COVID-19 may afford insights about potential intervention opportunities in future health crises. Objective This study examines factors associated with receptive injection equipment sharing among people who inject drugs in the context of COVID-19. Methods From August 2020 to January 2021, people who inject drugs were recruited from 22 substance use disorder treatment programs and harm reduction service providers in nine states and the District of Columbia to complete a survey that ascertained how the COVID-19 pandemic affected substance use behaviors. We used logistic regression to identify factors associated with people who inject drugs having recently engaged in receptive injection equipment sharing. Results One in four people who inject drugs in our sample reported having engaged in receptive injection equipment sharing in the past month. Factors associated with greater odds of receptive injection equipment sharing included: having a high school education or equivalent (adjusted odds ratio [aOR] = 2.14, 95% confidence interval [95% CI] 1.24, 3.69), experiencing hunger at least weekly (aOR = 1.89, 95% CI 1.01, 3.56), and number of drugs injected (aOR = 1.15, 95% CI 1.02, 1.30). Older age (aOR = 0.97, 95% CI 0.94, 1.00) and living in a non-metropolitan area (aOR = 0.43, 95% CI 0.18, 1.02) were marginally associated with decreased odds of receptive injection equipment sharing. Conclusions Receptive injection equipment sharing was relatively common among our sample during the early months of the COVID-19 pandemic. Our findings contribute to existing literature that examines receptive injection equipment sharing by demonstrating that this behavior was associated with factors identified in similar research that occurred before COVID. Eliminating high-risk injection practices among people who inject drugs requires investments in low-threshold and evidence-based services that ensure persons have access to sterile injection equipment.